THE IMPLEMENTATION OF PROBLEM BASED LEARNING IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT SMP NEGERI 1 SELESAI - Syartika Br.Pa (CV. Asry Persada Quality, 2024)
PBL learning is a teaching approach that uses real-world problems as a context for students to learn about critical learning and context-solving skills, as well as to acquire essential knowledge and concepts from the subject matter. With the PBL approach, the learning process is expected to take place naturally in the form of student activities to solve learning materials, not the transfer of knowledge from teacher to student. The purpose of this study was to describe the implementation of Problem Based Learning and Islamic Religious Education learning at SMP N 2 Selesai. In addition, it is also to find supporting factors, obstacles, and solutions to the implementation of Problem Based Learning in Islamic Religious Education learning at SMP Negeri 2 Selesai Pangandaran. This research can be classified as field research with a qualitative approach, namely research whose procedures produce descriptive data in the form of written or spoken words from people and observable behavior. Data collection techniques use observation, interviews, and documentation; while the data analysis technique used is descriptive qualitative. The conclusion of this study is: Islamic Religious Education learning with the implementation of Problem Based Learning carried out at SMP Negeri 2 Selesai has been running well. The supporting factors are the curriculum used, adequate facilities and infrastructure, teacher creativity, and environmental conditions. The inhibiting factors are the difficulty in generating ideas, lack of time availability, and differences in student understanding. While the solution is to provide direction to students by providing clues or clues to the answers, using time effectively and efficiently, and providing evaluation and repeating the material